Evolution law of the pore structure of CO2-H2O-coal in liquid CO2-ECBM - Xiaojiao Cheng; Hu Wen; Shixing Fan; Bocong Liu; Rijun Li; Yanhui Xu; Wen Wang (Journal of CO2 Utilization)
Liquid CO2 enhancing coalbed methane recovery (CO2-ECBM) is an effective and intrinsically reliable gas drainage technology. Injection of liquid CO2 into coal seam has the dual effect of increasing the permeability of the coal and rock and strengthening the recovery of gas, which is manifested primarily as “pressure cracking, low temperature frostbite, physical extraction and chemical corrosion, phase change pressurization, low viscosity permeability, competitive adsorption”. In this paper, the acidification and corrosion of CO2-H2O-coal was studied in physical and chemical extraction by experimental test and comparative analysis. The liquid CO2 acidification reference group and the variable group experiment were designed. On the basis of the pH value of the aqueous solution, the content of major elements and minerals in coal, the minerals involved in chemical reaction, and their specific gravity were deduced. Variation in pore volume, specific surface area, and pore fractal characteristics were quantitatively and qualitatively analyzed. The experimental results show that the higher the pressure, the higher the content of carbonic acid dissolved in water and the amount of H+ ionized by carbonic acid. The longer the reaction time, the greater the mineral content involved in the chemical reaction, and the H+ in the water sample is consumed in large quantities. The elements of Na, K, Ca, Mg, Al, Si, S, P, and Ti decreased with increasing pressure, and the maximum decreases were 0.004 %, 0.024 %, 1.095 %, 0.028 %, 0.220 %, 0.304 %, 0.006 %, 0.003 % and 0.029 %, respectively. The decrease in Ca element was the largest, indicating that Ca-bearing minerals participate in the reaction. Calcite, kaolinite, and illite were the main minerals involved in the chemical reaction of CO2-H2O-coal. The pores (d > 100 nm) and transition pores (10 < d < 100 nm) in the sample were further developed, and the pore volume increased significantly, forming a good gas migration channel. In addition, the number of new micropores (2 < d < 10 nm) increases, the specific surface area increases significantly, and the complexity of the pores increases, forming a good reservoir.